Pengembangan Perangkat Pembelajaran Evaluasi IPA Biologi Berbasis Digital Untuk Meningkatkan Kompetensi Keguruan Bagi Mahasiswa UNIMED - Ely Djulia; Sriadhi Sriadhi; Zulkifli Matondang; Janner Simarmata (Magister Pendidikan Biologi, Universitas Negeri Medan, 2021)
The development of information technology encourages the Teaching Faculty to produce Pre-service graduates who master professional and pedagogical competences enhanced by Information Communication Technology skills. This development research aims to develop evaluation instruments for digital-based education courses, especially evaluation. The ADDIE model is implemented to compile lesson plans and digital-based evaluation instruments. The research was conducted in five stages, namely the stages of analysis, material design, development, and implementation. The results of implementing digital-based evaluation instruments show efficiency and effectiveness for lecturers because the kahoot application provides direct reports for feedback and respondents are very motivated to answer the next point better and accurately. Respondents were impressed by the kahoot application with text, images, time allocation and also music, it was more attractive for respondents to focus more and think faster. Likewise with google forms with its efficiency and effectiveness for students and lecturers because it immediately reports immediately after the complete answer is submitted along with the output ranking. This research implies the importance of considering the use of digital-based evaluation instruments for better, more efficient, more effective feedback and follow-up for future evaluation courses.